Purchase Decision in the Online Shopping Application, Reviewed from Easy, Quality of Information, Culture, and Trust - Cantik Islamaya Fortuna; Fithri Setya Marwati (Almana : Jurnal Manajemen dan Bisnis, 2021)
The E-commerce sector is currently very developing and in demand because of the many advantages it has over conventional buying and selling activities. The purpose of this study was to determine the effect of easy, quality of information, culture, and trust on purchase decisions among users of the online shopping store applications in Surakarta. The sample can be calculated using the infinite formula method and the results are 96.04 people then rounded up to 100 respondents. This research is quantitative descriptive. This study will explain the relationship between the variables to be studied which are described by numbers. The F-test results show that Easy, Quality of Information, Culture, and Trust together have a significant effect on consumer purchasing decisions on the online shopping application Tokopedia. The t-test results show that easy has a positive and significant effect on purchasing decisions. This means that the higher the convenience of each consumer, the purchasing decision will increase. Quality Of Information has a positive and significant effect on purchasing decisions. This means that the higher the quality of information for each consumer, the purchasing decision will increase. Culture has a negative and significant effect on purchasing decisions. This means that cultural variables have a negative influence on purchasing decisions.